Interesting malignant renal tumours: a tripod of cases - Mamta Kumari; Haldar, Debaditya; Kumar, Mithilesh; Kumar, Bipin (International Journal of Research in Medical Sciences, 2023)
Renal malignancy is the 15th leading cause of annual deaths, with late detection and misdiagnosis leading to decreased patient survival. We hereby present three cases of malignant renal tumours which grabbed our attention because of their rarity and interesting presentation. Case 1-A 38 year old male presented with palpable lump in right flank, CT revealed a multilocular cystic lesion in right kidney, along with horse-shoe kidneys. In view of renal biopsy suggesting Tubulocystic carcinoma, patient underwent nephrectomy and diagnosis confirmed to be the same histomorphologically as well as immunohistochemically using AMACR and PR. Case 2-A 77-year-old male had lower urinary tract symptoms due to prostatomegaly, and a left renal mass and small hepatic cysts were detected incidentally. Kidney function was normal. Microscopy showed Chromophobe renal cell carcinoma, which was confirmed with immunohistochemical markers CK7 and CKIT. Case 3-A 50 year female presented with recurrent lump in her left flank, CT confirmed a huge left renal fossa mass. Biopsy showed features of malignant mesenchymal neoplasm consistent with leiomyosarcoma based on immunohistochemical panel of vimentin, h-Caldesmon, SMA, EMA, HMB-45 and S100, which helped in differentiating it from tumours like angiomyolipoma. Renal tumours have varied morphological overlapping and it is important to rule out close differentials using immunohistochemistry before coming to a diagnosis. Awareness of such presentations and findings can broaden our understanding of renal tumours which can help in early and accurate diagnosis for better outcome of the patient.